Causal Relationship Between Branched‐Chain Amino Acids and Hypertension: A Mendelian Randomization Study - Shiyuan Cai; Yuanyuan Fu; Jie Chen; Mingjie Tian; Xue Li (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background This study aimed to investigate the causal relationships between branched‐chain amino acids (BCAAs) and the risks of hypertension via meta‐analysis and Mendelian randomization analysis. Methods and Results A meta‐analysis of 32 845 subjects was conducted to evaluate the relationships between BCAAs and hypertension. In Mendelian randomization analysis, independent single‐nucleotide polymorphisms associated with BCAAs at the genome‐wide significance level were selected as the instrumental variables. Meanwhile, the summary‐level data for essential hypertension and secondary hypertension end points were obtained from the FinnGen study. As suggested by the meta‐analysis results, elevated BCAA levels were associated with a higher risk of hypertension (isoleucine: summary odds ratio, 1.26 [95% CI, 1.08–1.47]; leucine: summary odds ratio, 1.28 [95% CI, 1.07–1.52]; valine: summary odds ratio, 1.32 [95% CI, 1.12–1.57]). Moreover, the inverse variance‐weighted method demonstrated that an elevated circulating isoleucine level might be the causal risk factor for essential hypertension but not secondary hypertension (essential hypertension: odds ratio, 1.22 [95% CI, 1.12–1.34]; secondary hypertension: odds ratio, 0.96 [95% CI, 0.54–1.68]). Conclusions The increased levels of 3 BCAAs positively correlated with an increased risk of hypertension. Particularly, elevated isoleucine level is a causal risk factor for essential hypertension. Increased levels of leucine and valine also tend to increase the risk of essential hypertension, but further verification is still warranted.